The Influence of Roleplay Simulation on the Moral Development of Children Aged 8-9 Years Old - Aris Kurniyanto; Ahmad Yusuf (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background : A lack of moral development might increase negative moral behavior. Drama, as a part ofrole-play, can stimulate the moral development of children aged 8-9 years.Objective : The purpose of this study is to explain the effect of role-play on the moral development ofchildren aged 8-9 yearsMethod : This research applied pre-experimental one-group pre-post test design. The population in thisstudy was children aged 8-9 years with a total of 47 children. A sample of 15 respondents was taken usingpurposive sampling. The independent variable in this study is role-play stimulation, while the dependentvariable is the moral development of children aged 8-9 years. Data collection was done using observationsheets, then analyzed using Wilcoxon Signed Rank Test with significance ? = 0.05.Result: Wilcoxon Signed Rank Test shows that stimulation through role-play can influence the moraldevelopment of children aged 8-9 years with p = 0.001.Conclusion: The results of this study conclude that role-play stimulation can improve children’s moraldevelopment.